Preparation method of all-inorganic perovskite quantum dot polymer microsphere powder

By introducing crystallization reduction additives in the preparation of perovskite quantum dots, the crystallization rate is reduced and stability is improved, the problem of poor stability of perovskite quantum dots is solved, and stronger luminescence performance and longer service life are achieved.

CN119858937APending Publication Date: 2025-04-22HEFEI INNOVATION RES INST BEIHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311369342.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-20
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

In the prior art, the perovskite quantum dots have poor stability and are easily affected by temperature, humidity, oxygen and light, resulting in rapid decay of luminous performance.

Method used

Introduce crystal reduction aids to reduce the crystallization rate of perovskites, and form perovskite crystal structural phases through slow self-assembly to reduce defects and improve stability.

Benefits of technology

It significantly improves the stability and luminous intensity of perovskite quantum dots and extends the service life, especially in high temperature and high humidity environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858937A_ABST
    Figure CN119858937A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of all-inorganic perovskite quantum dot polymer microsphere powder, which comprises the following steps: S1, heating and stirring raw materials containing a cesium source, a lead source, a halogen ligand, a polymer, a polar solvent and a crystallization retarder to form a precursor solution; s2, performing spray drying on the precursor solution in the step S1 to form microsphere polymer powder; and S3, carrying out secondary curing on the microsphere polymer powder in the step S2, and grinding to obtain the all-inorganic perovskite quantum dot polymer microsphere powder. The crystallization speed of the perovskite is reduced by introducing the crystallization speed-reducing auxiliary agent, and especially under the condition that the solubility of the cesium bromide raw material in the polar solvent is not high, the problems of low quantum dot generation efficiency, many defects, weak luminescence and poor stability caused by precipitation and crystallization in advance are solved. And an in-situ high-temperature spraying method is used, so that the tedious and expensive synthesis process of high-temperature heat injection is avoided, and the quantum dots are well embedded in the surfaces and pores of the polymer microspheres.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a method for preparing all-inorganic perovskite quantum dot polymer microsphere powder, and belongs to the technical field of preparation of new optoelectronic display materials. Background Art

[0002] As a new type of nanomaterial with unique optical properties, quantum dot film can accurately convert high-energy blue light into red and green light. Quantum dots can form a film on the LED backlight of the LCD display, and can emit full-spectrum light using blue LEDs. By fine-tuning the backlight, the color gamut performance can be greatly improved, and the brightness can be increased to make the colors more vivid.

[0003] According to market research, the sales revenue of China's new display quantum dot film market will reach 1.5198 million yuan in 2022, and it is expected to reach 219.97 million yuan in 2029, with a compound annual growth rate of 4.02% during 2023-2029. The core manufacturers in the Chinese market include Jizhi Technology, Nanocrystal Technology and Zhongke Natong. In terms of revenue, the top three manufacturers in the Chinese market in 2022 account for approximately 79.14% of the market share. In terms of product types, cadmium quantum dots occupy an important position, and it is expected that the share will reach 56.39% in 2029. At the same time, in terms of application, the share of televisions in 2022 is about 94.91%, and the annual compound growth rate in the next few years (2024-2029) is about 3.93%. The optical film of the perovskite quantum dot system has the advantages of cadmium-free green and environmental protection, simple synthesis, low cost, high absorbance, and commercial life. It is gradually replacing cadmium-based quantum dot film products and has immeasurable market opportunities.

[0004] Among the methods for in-situ preparation of perovskite quantum dots, the in-situ spray method is currently widely used. The liquid is atomized by transmitting it to the nozzle through a liquid phase system. The entire cavity is a high-temperature thermal field, which efficiently removes most of the solvent in the droplets. The raw materials of the perovskite precursor need to crystallize from the solvent system due to supersaturation, and combine with each other to form a perovskite crystal structure phase. The physical space load of the polymer microspheres is collected by a cyclone collector to obtain a photoluminescent powder of a quantum dot and polymer composite.

[0005] The knowledge of perovskite quantum dots can generally be extended to luminescent particles of nanoparticle size. The system is mainly divided into two categories, one is organic / inorganic hybrid lead halide perovskite (MAPbX3, FAPbX3; X = Cl, Br, I); the other is all-inorganic perovskite CsPbX3 (X = Cl, Br, I). Perovskite quantum dots generally have the advantages of ultra-high quantum dot yield, narrow emission half-peak width, short fluorescence lifetime, high crystallinity, high electron-hole mobility, and low price. They are widely used in the field of light-emitting diodes and photovoltaic cells. However, the disadvantages of perovskite quantum dots are also obvious. The stability of quantum dot materials without good design and control is poor. They are particularly susceptible to the influence of temperature, humidity, oxygen, light and other environmental factors, which has a rapid decay effect on the luminescence performance.

[0006] First, the A position of organic / inorganic hybrid lead halide perovskite quantum dots has an organic part, which is particularly easy to decompose under high temperature and high humidity, resulting in lattice defects and obvious degradation of luminescence performance. Moreover, if quantum dots are not encapsulated by polymers or using barrier films, it is difficult to achieve long-term use, and the service life is short. Summary of the invention

[0007] According to one aspect of the present application, a method for preparing an all-inorganic perovskite quantum dot polymer microsphere powder is provided. The preparation method of the present application creatively introduces a crystallization deceleration aid, which can help reduce the crystallization rate of the perovskite, slow down the premature precipitation of the raw materials into a mixed phase, and enable more precursor raw materials to self-assemble into a perovskite crystal structure phase at a low speed, thereby solving the problem of low efficiency, many defects, weak luminescence and poor stability of quantum dots generated due to premature crystallization in the prior art of the in-situ spray method.

[0008] This application adopts the following technical solutions:

[0009] A method for preparing all-inorganic perovskite quantum dot polymer microsphere powder, characterized in that it comprises the following steps:

[0010] S1. heating and stirring raw materials containing a cesium source, a lead source, a halogen ligand, a polymer, a polar solvent, and a crystallization moderator to form a precursor solution;

[0011] S2, spray drying the precursor solution in step S1 to form microsphere polymer powder;

[0012] S3, secondary aging and grinding the microsphere polymer powder in step S2 to obtain the all-inorganic perovskite quantum dot polymer microsphere powder.

[0013] Optionally, the precursor solution is a stable phase solution of a quantum dot polymer precursor.

[0014] The present application introduces a crystallization deceleration aid, which reduces the crystallization rate of perovskite, so that more precursor raw materials can self-assemble into a perovskite crystal structure phase at a low speed, with fewer defects, stronger luminescence and better stability. In particular, when the cesium bromide raw material has a low solubility in polar solvents, it can help slow down the premature precipitation of cesium bromide into a mixed phase, thereby solving the problem of low efficiency, many defects, weak luminescence and poor stability in the generation of quantum dots caused by premature crystallization.

[0015] The principle of the crystallization deceleration aid is to dissolve in a liquid polar solvent, coordinate with cesium and lead sources, increase solubility and precipitation rate in the solvent, and ensure reaction with the slowly precipitated precursor to generate a luminescent perovskite quantum dot crystal structure phase with high conversion rate and high utilization rate of precursor raw materials.

[0016] Preferably, from the perspective of material design, a structurally stable and fully inorganic CsPbBr3 component is selected. The A-position cation is more stable and coordinates with cesium bromide to increase the solubility in the solvent, ensuring that it reacts with the slowly precipitated precursor to generate a luminescent CsPbBr3 crystal structure phase, with a high conversion rate and high utilization rate of the precursor raw materials.

[0017] Optionally, in step S1, the temperature of the heating and stirring is 40-60°C.

[0018] Optionally, in step S1, the crystallization moderator is selected from at least one of polyethylene glycol (PEG), polyetheramine, L-carnitine, and sulfobetaine.

[0019] The above-mentioned deceleration aids all contain 2+ and Cs + Strongly coordinating groups.

[0020] Optionally, in step S1, the weight ratio of the cesium source, the lead source, the halogen ligand, the polymer, the polar solvent, and the crystallization moderator is:

[0021] (4.2~5.2):(3.8~4.8):1:(70~90):(1100~1300):(23~32).

[0022] Optionally, in step S1, the weight ratio of the crystallization moderator to the cesium source is 1:0.13-0.2.

[0023] Optionally, in step S1, the weight ratio of the crystallization moderator to the cesium source is selected from any value of 1:0.13, 1:0.14, 1:0.15, 1:0.16, 1:0.17, 1:0.18, 1:0.19, 1:0.2, or any range between the two.

[0024] Optionally, in the all-inorganic perovskite quantum dot polymer microsphere powder, the all-inorganic perovskite quantum dots are CsPbCl3, CsPbCl3-x Br x 、CsPbBr3、CsPbBr 3-y I y 、CsPbI3、CsSnCl3、CsSnCl 3-x Br x 、CsSnBr3、CsSnBr 3-y I y , CsSnI3 or at least one of the following.

[0025] Where 0 <x<3,0<y<3。

[0026] Optionally, in step S1, the cesium source is selected from at least one of cesium bromide, cesium acetate, cesium methanesulfonate, cesium pivalate, cesium formate, cesium molybdate, and cesium silicate.

[0027] Optionally, in step S1, the lead source is selected from at least one of lead bromide, lead acetate, lead fluoroborate, lead carbonate, lead tartrate, lead thiocyanate, lead citrate, and lead molybdate.

[0028] Optionally, in step S1, the halogen ligand is selected from at least one of didodecyldimethylammonium bromide (DDAB), phenethylammonium bromide (PEABr), octylammonium bromide (OABr), tetrabutylammonium bromide (TBABr), tetrabutylammonium chloride (TBACl), octylammonium iodide (OAI), and octylammonium chloride (OACl).

[0029] Optionally, in step S1, the polymer is selected from at least one of polymethyl methacrylate (PMMA), polyvinylidene fluoride (PVDF), polystyrene (PS), polycarbonate (PC), styrene-methyl methacrylate copolymer (MS), polyethylene terephthalate (PET), polypropylene (PP), polyethylene (PE), acrylonitrile resin (PAN), and acrylonitrile-styrene copolymer (AS).

[0030] Optionally, in step S1, the polar solvent is selected from at least one of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO).

[0031] Optionally, the specific process of spray drying in step S2 includes: transporting the precursor solution in step S1 to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, breaking it up and atomizing it into droplets using high-pressure nitrogen, and subjecting it to a high-temperature thermal field to instantly remove most of the polar solvent, so that the precursor raw material can be ionized and precipitated and crystallized. The whole process involves the process of droplets becoming smaller and atomized, and instant drying in a high-temperature thermal field, forming microsphere polymer powder that is collected by a cyclone collector of the spray equipment.

[0032] Optionally, in step S2, the spray drying conditions include: the temperature of the spray equipment is 60-100°C, the temperature of the spray equipment is 70-100 MPa, and the fan frequency of the spray equipment is 20-50 Hz.

[0033] The in-situ high-temperature spraying method avoids the tedious and expensive synthesis process of high-temperature hot injection, and the quantum dots are well embedded in the surface and pores of the polymer microspheres. The final perovskite quantum dot film with excellent optical properties and high stability is formed. The use of a water-blocking and oxygen-blocking polymer matrix to encapsulate the quantum dots has a certain encapsulation effect. In addition, the use of a water-blocking and oxygen-blocking barrier film for encapsulation can make the quantum dots of the green light system have high stability and are not afraid of damage from strong blue light, high temperature, and high humidity environments.

[0034] Optionally, in step S2, the spray drying conditions include: the temperature of the spray equipment is selected from any value of 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, or any range therebetween.

[0035] Optionally, in step S2, the spray drying conditions include: the temperature of the spray equipment is selected from any value of 70MPa, 75MPa, 80MPa, 85MPa, 90MPa, 95MPa, 100MPa, or any range therebetween.

[0036] Optionally, in step S2, the spray drying conditions include: a fan frequency of the spray equipment is selected from any value of 20 Hz, 25 Hz, 30 Hz, 35 Hz, 40 Hz, 45 Hz, 50 Hz, or any range value therebetween.

[0037] Optionally, in step S3, the secondary aging conditions include: the secondary aging temperature is 80-130° C., and the secondary aging time is 5-20 min.

[0038] Optionally, in step S3, the secondary aging conditions include: the secondary aging temperature is selected from any value of 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, or any range therebetween.

[0039] Optionally, in step S3, the secondary ripening conditions include: the secondary ripening time is selected from any value of 5 min, 8 min, 10 min, 13 min, 15 min, 18 min, 20 min, or any range value therebetween.

[0040] Optionally, in step S3, the specific steps of the secondary aging include: spreading the white microsphere polymer powder obtained in step S2 on tin foil, placing it in a blast oven for high-temperature baking to remove the solvent for a secondary time, regrowing the crystal structure, converting the white powder into green powder, cooling it to room temperature, grinding it with an agate mortar, and sieving and bottling it.

[0041] The present application aims to provide a method for preparing high-efficiency and high-stability all-inorganic perovskite quantum dot polymer microsphere powder by in-situ spraying of a crystallization deceleration aid, and in particular to provide an effective solution to the problems of poor stability of green powder and insufficient light conversion efficiency in perovskite quantum dot films.

[0042] The beneficial effects of this application include:

[0043] (1) The preparation method of the all-inorganic perovskite quantum dot polymer microsphere powder provided in the present application introduces a method of a crystallization decelerating agent, and solves the problems of low efficiency, many defects, weak luminescence, and poor stability of quantum dots generated due to premature crystallization. In particular, the problem of excessive precipitation of cesium bromide in polar solvents to generate impurities is solved. The crystallization decelerating agent is used to coordinate with cesium bromide in the solvent system to improve its solubility in the solvent, thereby ensuring that it reacts with the slowly precipitated precursor to generate a luminescent CsPbBr3 crystal structure phase, with a high conversion rate and a high utilization rate of the precursor raw materials.

[0044] (2) The preparation method of the present application is more stable in material design than organic / inorganic hybrid lead halide perovskite quantum dots because the A position is an inorganic Cs ion, which is less susceptible to damage and decomposition by high temperature and high humidity.

[0045] (3) The preparation method of the present application utilizes polymers for in-situ generation and physical space loading of quantum dots, which protects the quantum dots to a certain extent and prevents them from being damaged by water vapor and oxygen. At the same time, the large particle size of the polymer can be well collected by the cyclone collector of the spray equipment.

[0046] (4) This application introduces for the first time the combination of a crystallization deceleration aid and a perovskite crystallization spray, further promoting the product development direction of the combination of high molecular polymers and quantum dot materials in this field. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 This is a schematic diagram of the in-situ high-temperature spraying process of Example 1 of the present application. DETAILED DESCRIPTION

[0048] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0049] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0050] Unless otherwise specified, conventional methods were used for testing and instrument settings were those recommended by the manufacturer.

[0051] According to one embodiment of the present application, the all-inorganic perovskite quantum dot polymer microsphere powder can be made into a quantum dot film for optical performance testing and aging performance testing, and the preparation method includes:

[0052] The prepolymer, monomer, photoinitiator, and all-inorganic perovskite quantum dot polymer microsphere powder are mixed and stirred in a certain proportion, and the coating machine is used to set the thickness to 20-60um, and the glue is coated on the PET surface of the barrier diffusion film, both above and below are barrier diffusion films, and the energy is 500-2500mj / cm 2 Curing is done with 365nm UV lamp.

[0053] The prepolymer may be selected from aliphatic polyurethane acrylate, aliphatic polyurethane hexaacrylate, tin-free aliphatic polyurethane diacrylate, aromatic polyurethane acrylate, aromatic polyurethane hexaacrylate, fluorine-modified polyurethane acrylate, silicone-modified polyurethane acrylate, 2-hydroxy-3-phenoxypropyl acrylate, epoxy acrylate, modified epoxy acrylate, epoxy methacrylate, fatty acid-modified epoxy acrylate, modified bisphenol A epoxy acrylate, phenolic epoxy acrylate, epoxy soybean oil acrylate, fatty acid-modified polyester hexaacrylate, fatty acid-modified polyester acrylate, At least one of esters, chlorinated polyester resins, modified polyester acrylates, amine-modified polyester acrylates, hyperbranched polyester acrylates, rosin-modified polyester acrylates, tertiary amine acrylates, hot-melt pure acrylate resins, pure acrylic resins, organic-inorganic hybrid acrylate oligomers, melamine acrylates, silicon-modified polyurethane acrylates, and polycaprolactone acrylates; the monomers may be selected from 4-tert-butyl cyclohexyl acrylate, methacrylate ethylene urea ethoxylate, m-phenoxybenzyl acrylate, dicyclopentenyl acrylate, dicyclopentenyl ethoxylated acrylate, ethoxylated phenoxy acrylate At least one of acrylate, 3,3,5-trimethylcyclohexyl acrylate, o-phenylphenoxyethyl acrylate, 2-(p-isopropylphenyl-phenoxy)-ethyl acrylate, ethoxyethoxyethyl acrylate, 3-hydroxy-2,2-dimethylpropyl-3-hydroxy-2,2-dimethylpropyl acrylate, tricyclodecane dimethanol diacrylate, dioxane diol diacrylate, polypropylene glycol (700) diacrylate, 1,6-hexanediol diacrylate, ethoxylated 1,6-hexanediol diacrylate, and dipropylene glycol diacrylate; the photoinitiator can be selected from 2-methyl-1- [4-(methylthio)phenyl]-2-morpholinyl]-1-propanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, benzoin dimethyl ether, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxy-cyclohexyl-phenyl ketone, benzophenone, isopropylthioxanthone (2,4 isomer mixture), ethyl 4-(N,N-dimethylamino)benzoate, isooctyl 4-(N,N-dimethyl)benzoate, 2-isopropylthioxanthone, 2-benzyl-2-(dimethylamino)-4-morpholine, 4-phenylxylene ketone, at least one of methyl o-benzoylbenzoate.

[0054] Example 1 (experimental group - adding crystallization deceleration agent PEG): CsPbBr3@PMMA-PEG green quantum dot microspheres

[0055] (1) Preparation of quantum dot polymer precursor solution: The six components of quantum dot precursor raw materials, cesium bromide, lead bromide, octyl ammonium bromide, PMMA, DMF, and PEG, were weighed according to a mass ratio (4.7:4.3:1:80:1250:28), heated at 50°C, stirred, and mixed to form a quantum dot polymer precursor solution with a stable phase.

[0056] (2) High-temperature spray atomization droplets to remove solvent: The quantum dot polymer precursor solution prepared in step (1) is transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and is atomized into droplets using high-pressure nitrogen (80 MPa). The solution is then subjected to a high-temperature thermal field (70°C) to instantly remove most of the polar solvent, allowing the precursor raw materials to ionize and crystallize. The entire process involves droplets becoming smaller and atomized, and then being instantly dried in a high-temperature thermal field, forming microsphere polymer powder that is collected by a cyclone collector of the spray equipment.

[0057] (3) Secondary aging growth: The white microsphere polymer powder obtained in step (2) is spread on tin foil and placed in a forced air oven for high temperature (110°C) baking for 10 min to remove the solvent for the second time. The crystal structure grows again and the white powder turns into green powder. The powder is cooled to room temperature, ground with an agate mortar, sieved and bottled.

[0058] (4) Preparation of quantum dot film: prepolymer (fluorine-modified polyurethane acrylate), monomer (dicyclopentenyl ethoxylated acrylate), photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and green quantum dot polymer powder were mixed and stirred in a mass ratio of (3:2:0.5:1), and the coating machine was set to a thickness of 50 μm. The glue was coated on the PET surface of the barrier diffusion film, with barrier diffusion film on both sides, and cured by 365 nm ultraviolet lamp with an energy of 1000 mj / cm 2 , an optical perovskite quantum dot film that can be used for optical performance testing and aging performance testing was obtained and marked as CsPbBr3@PMMA-PEG microsphere powder.

[0059] Example 2 (experimental group - adding crystallization deceleration agent PEG): CsPbBr3@PVDF-PEG green quantum dot microspheres

[0060] (1) Preparation of quantum dot polymer precursor solution: The six components of quantum dot precursor raw materials, cesium bromide, lead bromide, octyl ammonium bromide, PVDF, DMF, and PEG, are weighed according to a mass ratio (4.7:4.3:1:80:1250:28), heated at 50°C, stirred, and mixed to form a quantum dot polymer precursor solution with a stable phase.

[0061] (2) High-temperature spray atomization droplets to remove solvent: The quantum dot polymer precursor solution prepared in step (1) is transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and is atomized into droplets using high-pressure nitrogen (80 MPa). The solution is then subjected to a high-temperature thermal field (70°C) to instantly remove most of the polar solvent, allowing the precursor raw materials to ionize and crystallize. The entire process involves droplets becoming smaller and atomized, and then being instantly dried in a high-temperature thermal field, forming microsphere polymer powder that is collected by a cyclone collector of the spray equipment.

[0062] (3) Secondary aging growth: The white microsphere polymer powder obtained in step (2) is spread on tin foil and placed in a forced air oven for high temperature (110°C) baking for 10 min to remove the solvent for the second time. The crystal structure grows again and the white powder turns into green powder. The powder is cooled to room temperature, ground with an agate mortar, sieved and bottled.

[0063] (4) Preparation of quantum dot film: prepolymer (fluorine-modified polyurethane acrylate), monomer (dicyclopentenyl ethoxylated acrylate), photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and green quantum dot polymer powder were mixed and stirred in a mass ratio of (3:2:0.5:1), and the coating machine was set to a thickness of 50 μm. The glue was coated on the PET surface of the barrier diffusion film, with barrier diffusion film on both sides, and cured by 365 nm ultraviolet lamp with an energy of 1000 mj / cm 2 , an optical perovskite quantum dot film that can be used for optical performance testing and aging performance testing was obtained and marked as CsPbBr3@PVDF-PEG microsphere powder.

[0064] Example 3 (experimental group - adding crystallization deceleration agent PEG): CsPbBr3@PAN-PEG green quantum dot microspheres

[0065] (1) Preparation of quantum dot polymer precursor solution: The six components of quantum dot precursor raw materials, cesium bromide, lead bromide, octyl ammonium bromide, PAN, DMF, and PEG, are weighed according to a mass ratio (4.7:4.3:1:80:1250:28), heated at 50°C, stirred, and mixed to form a quantum dot polymer precursor solution with a stable phase.

[0066] (2) High-temperature spray atomization droplets to remove solvent: The quantum dot polymer precursor solution prepared in step (1) is transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and is atomized into droplets using high-pressure nitrogen (80 MPa). The solution is then subjected to a high-temperature thermal field (70°C) to instantly remove most of the polar solvent, allowing the precursor raw materials to ionize and crystallize. The entire process involves droplets becoming smaller and atomized, and then being instantly dried in a high-temperature thermal field, forming microsphere polymer powder that is collected by a cyclone collector of the spray equipment.

[0067] (3) Secondary aging growth: The white microsphere polymer powder obtained in step (2) is spread on tin foil and placed in a forced air oven for high temperature (110°C) baking for 10 min to remove the solvent for the second time. The crystal structure grows again and the white powder turns into green powder. The powder is cooled to room temperature, ground with an agate mortar, sieved and bottled.

[0068] (4) Preparation of quantum dot film: prepolymer (fluorine-modified polyurethane acrylate), monomer (dicyclopentenyl ethoxylated acrylate), photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and green quantum dot polymer powder were mixed and stirred in a mass ratio of (3:2:0.5:1), and the coating machine was set to a thickness of 50 μm. The glue was coated on the PET surface of the barrier diffusion film, with barrier diffusion film on both sides, and cured by 365 nm ultraviolet lamp with an energy of 1000 mj / cm 2 , an optical perovskite quantum dot film that can be used for optical performance testing and aging performance testing was obtained and marked as CsPbBr3@PMMA-PAN microsphere powder.

[0069] Example 4 (experimental group - adding crystallization deceleration agent PEG): CsPbBr3@AS-PEG green quantum dot microspheres

[0070] (1) Preparation of quantum dot polymer precursor solution: The six components of quantum dot precursor raw materials, cesium bromide, lead bromide, octyl ammonium bromide, AS, DMF, and PEG, were weighed according to a mass ratio (4.7:4.3:1:80:1250:28), heated at 50°C, stirred, and mixed to form a quantum dot polymer precursor solution with a stable phase.

[0071] (2) High-temperature spray atomization droplets to remove solvent: The quantum dot polymer precursor solution prepared in step (1) is transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and is atomized into droplets using high-pressure nitrogen (80 MPa). The solution is then subjected to a high-temperature thermal field (70°C) to instantly remove most of the polar solvent, allowing the precursor raw materials to ionize and crystallize. The entire process involves droplets becoming smaller and atomized, and then being instantly dried in a high-temperature thermal field, forming microsphere polymer powder that is collected by a cyclone collector of the spray equipment.

[0072] (3) Secondary aging growth: The white microsphere polymer powder obtained in step (2) is spread on tin foil and placed in a forced air oven for high temperature (110°C) baking for 10 min to remove the solvent for the second time. The crystal structure grows again and the white powder turns into green powder. The powder is cooled to room temperature, ground with an agate mortar, sieved and bottled.

[0073] (4) Preparation of quantum dot film: prepolymer (fluorine-modified polyurethane acrylate), monomer (dicyclopentenyl ethoxylated acrylate), photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and green quantum dot polymer powder were mixed and stirred in a mass ratio of (3:2:0.5:1), and the coating machine was set to a thickness of 50 μm. The glue was coated on the PET surface of the barrier diffusion film, with barrier diffusion film on both sides, and cured by 365 nm ultraviolet lamp with an energy of 1000 mj / cm 2 , an optical perovskite quantum dot film that can be used for optical performance testing and aging performance testing was obtained and marked as CsPbBr3@AS-PAN microsphere powder.

[0074] Example 5 (experimental group - adding crystallization deceleration agent PEG): CsPbBr3@AS-PC green quantum dot microspheres

[0075] (1) Preparation of quantum dot polymer precursor solution: The six components of quantum dot precursor raw materials, cesium bromide, lead bromide, octyl ammonium bromide, PC, DMF, and PEG, were weighed according to a mass ratio (4.7:4.3:1:80:1250:28), heated at 50°C, stirred, and mixed to form a quantum dot polymer precursor solution with a stable phase.

[0076] (2) High-temperature spray atomization droplets to remove solvent: The quantum dot polymer precursor solution prepared in step (1) is transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and is atomized into droplets using high-pressure nitrogen (80 MPa). The solution is then subjected to a high-temperature thermal field (70°C) to instantly remove most of the polar solvent, allowing the precursor raw materials to ionize and crystallize. The entire process involves droplets becoming smaller and atomized, and then being instantly dried in a high-temperature thermal field, forming microsphere polymer powder that is collected by a cyclone collector of the spray equipment.

[0077] (3) Secondary aging growth: The white microsphere polymer powder obtained in step (2) is spread on tin foil and placed in a forced air oven for high temperature (110°C) baking for 10 min to remove the solvent for the second time. The crystal structure grows again and the white powder turns into green powder. The powder is cooled to room temperature, ground with an agate mortar, sieved and bottled.

[0078] (4) Preparation of quantum dot film: prepolymer (fluorine-modified polyurethane acrylate), monomer (dicyclopentenyl ethoxylated acrylate), photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and green quantum dot polymer powder were mixed and stirred in a mass ratio of (3:2:0.5:1), and the coating machine was set to a thickness of 50 μm. The glue was coated on the PET surface of the barrier diffusion film, with barrier diffusion film on both sides, and cured by 365 nm ultraviolet lamp with an energy of 1000 mj / cm 2 , an optical perovskite quantum dot film that can be used for optical performance testing and aging performance testing is obtained and marked as CsPbBr3@PC-PAN microsphere powder.

[0079] Comparative Example 1 (Control Group - No Crystallization Deceleration Aid): CsPbBr3@PMMA-Num Green Quantum Dot Microspheres

[0080] (1) Preparation of quantum dot polymer precursor solution: The five components of quantum dot precursor raw materials, cesium bromide, lead bromide, octyl ammonium bromide, PMMA, and DMF, are weighed according to a mass ratio (4.7:4.3:1:80:1250), heated at 50°C, stirred, and mixed to form a quantum dot polymer precursor solution with a stable phase.

[0081] (2) High-temperature spray atomization droplets to remove solvent: The quantum dot polymer precursor solution prepared in step (1) is transported to the nozzle of the spray equipment through a peristaltic pump and a rubber tube, and is atomized into droplets using high-pressure nitrogen (80 MPa). The solution is then subjected to a high-temperature thermal field (70°C) to instantly remove most of the polar solvent, allowing the precursor raw materials to ionize and crystallize. The entire process involves droplets becoming smaller and atomized, and then being instantly dried in a high-temperature thermal field, forming microsphere polymer powder that is collected by a cyclone collector of the spray equipment.

[0082] (3) Secondary aging growth: The white microsphere polymer powder obtained in step (2) is spread on tin foil and placed in a forced air oven for high temperature (110°C) baking for 10 min to remove the solvent for the second time. The crystal structure grows again and the white powder turns into green powder. The powder is cooled to room temperature, ground with an agate mortar, sieved and bottled.

[0083] (4) Preparation of quantum dot film: prepolymer (fluorine-modified polyurethane acrylate), monomer (dicyclopentenyl ethoxylated acrylate), photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), and green quantum dot polymer powder were mixed and stirred in a mass ratio of (3:2:0.5:1), and the coating machine was set to a thickness of 50 μm. The glue was coated on the PET surface of the barrier diffusion film, with barrier diffusion film on both sides, and cured by 365 nm ultraviolet lamp with an energy of 1000 mj / cm2 , an optical perovskite quantum dot film that can be used for optical performance testing and aging performance testing is obtained and marked as CsPbBr3@PMMA-Num microsphere powder.

[0084] Test Example 1

[0085] The films CsPbBr3@PMMA-PEG, CsPbBr3@PVDF-PEG, CsPbBr3@PAN-PEG, CsPbBr3@AS-PEG, CsPbBr3@PC-PEG, and CsPbBr3@PMMA-Num containing all-inorganic perovskite quantum dot polymer microsphere powder prepared in Examples 1 to 5 and Comparative Example 1 were subjected to optical performance and aging tests, respectively. The results are shown in Table 1. From the data, it can be seen that CsPbBr3@PMMA-PEG uses PMMA as a polymer matrix, which has the highest light conversion efficiency and the best wet heat stability and light stability. It is sufficient to show that the use of a crystallization retardant is crucial for the high efficiency and high stability of all-inorganic CsPbBr3 perovskite quantum dots prepared by the in-situ spray method, and can be extended to a variety of polymer systems.

[0086] Table 1: Optical properties and aging properties of the corresponding tests of the embodiment

[0087]

[0088]

[0089] a The test conditions are: temperature 65 degrees, humidity 95%, 1000h;

[0090] b The test conditions are: temperature 45 degrees, humidity 95%, light intensity 38W / m 2 (450nm), 1000h.

[0091] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing all-inorganic perovskite quantum dot polymer microsphere powder, characterized in that: The steps include: S1. heating and stirring raw materials containing a cesium source, a lead source, a halogen ligand, a polymer, a polar solvent, and a crystallization moderator to form a precursor solution; S2, spray drying the precursor solution in step S1 to form microsphere polymer powder; S3, secondary aging and grinding the microsphere polymer powder in step S2 to obtain the all-inorganic perovskite quantum dot polymer microsphere powder.

2. The preparation method according to claim 1, characterized in that In step S1, the crystallization moderator is selected from at least one of polyethylene glycol, polyetheramine, L-carnitine and sulfobetaine.

3. The preparation method according to claim 1, characterized in that In step S1, the weight ratio of the cesium source, the lead source, the halogen ligand, the polymer, the polar solvent, and the crystallization moderator is: (4.2~5.2):(3.8~4.8):1:(70~90):(1100~1300):(23~32)。 4. The preparation method according to claim 1, characterized in that In the all-inorganic perovskite quantum dot polymer microsphere powder, the all-inorganic perovskite quantum dots are CsPbCl3, CsPbCl 3-x Br x 、CsPbBr3、CsPbBr 3-y I y 、CsPbI3、CsSnCl3、CsSnCl 3-x Br x 、CsSnBr3、CsSnBr 3-y I y , CsSnI3 or at least one of the following.

5. The preparation method according to claim 1, characterized in that: In step S1, the cesium source is selected from at least one of cesium bromide, cesium acetate, cesium methanesulfonate, cesium pivalate, cesium formate, cesium molybdate, and cesium silicate.

6. The preparation method according to claim 1, characterized in that: In step S1, the lead source is selected from at least one of lead bromide, lead acetate, lead fluoroborate, lead carbonate, lead tartrate, lead thiocyanate, lead citrate, and lead molybdate.

7. The preparation method according to claim 1, characterized in that: In step S1, the halogen ligand is selected from at least one of DDAB, PEABr, OABr, TBABr, TBACl, OAI, and OACl.

8. The preparation method according to claim 1, characterized in that: In step S1, the polymer is selected from at least one of PMMA, PVDF, PS, PC, MS, PET, PP, PE, PAN, and AS.

9. The preparation method according to claim 1, characterized in that: In step S2, the spray drying conditions include: the temperature of the spray equipment is 60-100°C, the pressure of the spray equipment is 70-100 MPa, and the fan frequency of the spray equipment is 20-50 Hz.

10. The preparation method according to claim 1, characterized in that: In step S3, the secondary aging conditions include: the secondary aging temperature is 80-130° C., and the secondary aging time is 5-20 min.